Audit Delay Melalui Ukuran Perusahaan Sebagai Variabel Moderasi: Profitabilitas, Kompleksitas Operasi Dan Leverage - Anisa Marsella Licodata (Journal of Business and Economics (JBE) UPI YPTK, 2019)
This study aims to determine the effect of Profitability, Operational Complexity, and Leverage on Audit Delay with Company Size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period. The type of data used is secondary data in the form of financial statements of manufacturing companies. The sample in this study found 50 manufacturing companies with a study period of 5 years. The analytical method used in this study is panel data regression analysis with Fixxed Effect Estimation results using Eviews 9. The results of this study indicate that Profitability has no significant effect on Audit Delay, while Operational Complexity and Leverage have a significant effect on Audit Delay. And Company Size is able to moderate Profitability and Leverage, while operating modifications are not able to be moderated by Company Size